Exploring Qur’anic Mathematical Miracles through Median Analysis on Surah As-Sajdah and Surah Al-Insan - Muhammad Zia Alghar; Putri Yasin Nasution; Milda Sari; Abdul Haris Nasution (Studia Quranika, 2026)
The miracles (i'jaz) in the Qur'an can be examined not only from a linguistic perspective, but also from a numerical perspective. One interesting phenomenon is the hadith about the virtue of reciting Surah As-Sajdah and Surah Al-Insan during the Fajr prayer on Friday. This study aims to explore these two surahs through a mathematical approach. A quantitative descriptive method with median analysis was used in this study. The data examined included the number of verses and words in Surah As-Sajdah, Surah Al-Insan, and the range of surahs between the two. The integration model used was mathematics to explore the Qur'an. The results of the study show three main findings. First, the median word in Surah As-Sajdah falls on verse 15, precisely on the word sujjada, which means prostration, and is located in the verse of prostration. Second, both the median verse and the median word in Surah Al-Insan consistently point to verse 16. Third, the median verse from the beginning of Surah As-Sajdah to the end of Surah Al-Insan points to Surah Muhammad verse 18, which talks about the signs of the Day of Judgment, in line with the belief that the Day of Judgment will occur on Friday. These findings show that simple mathematical analyses such as the median can be applied to reveal the regularity and numerical wonders in the Qur'an. This research contributes to the study of the i'jaz of the Qur'an from a mathematical perspective while opening up opportunities for the development of Qur'an-based mathematics learning integration.